[Effect of invitation to colonoscopy screening on Risks of Colorectal Cancer and Related Death (the NordICC study): Critical reading:] - Zela-Coila , Frank (2024)
Presentation: The NordICC study aimed to evaluate the long-term effects, with a 10-year follow-up, of inviting individuals aged 55 to 64 years to undergo a single colonoscopy screening for colorectal cancer (CC) compared to those who were not invited and did not undergo screening. Study findings: The group that received the colonoscopy screening invitation had lower risk of CC in comparison to the group that did not undergo screening. Critical commentary: The study's eligibility criteria closely resembled real-life scenarios. However, the inclusion of participants with CC risk factors and the potential differential effects in this subgroup remain unclear. The invitation for a single colonoscopy screening did not result in clinically important benefits in terms of CC risk, CC mortality, and all-cause mortality. On the other hand, complications associated with the screening procedure were infrequent or negligible. It is important to note a high risk of bias in the blinding-related domains.